Device for respiration activity measurement enables the determination of oxygen transfer rates of microbial cultures in shaken 96‐deepwell microtiter plates. Issue 3 (7th January 2022) - Dinger, Robert; Lattermann, Clemens; Flitsch, David; Fischer, Jan P.; Kosfeld, Udo; Büchs, Jochen
Abstract: Mini‐bioreactors with integrated online monitoring capabilities are well established in the early stages of process development. Mini‐bioreactors fulfil the demand for high‐throughput‐applications and a simultaneous reduction of material costs and total experimental time. One of the most essential online monitored parameters is the oxygen transfer rate (OTR). OTR‐monitoring allows fast characterization of bioprocesses and process transfer to larger scales. Currently, OTR‐monitoring on a small‐scale is limited to shake flasks and 48‐well microtiter plates (MTP). Especially, 96‐deepwell MTP are used for high‐throughput‐experiments during early‐stage bioprocess development. However, a device for OTR monitoring in 96‐deepwell MTP is still not available. To determine OTR values, the measurement of the gas composition in each well of a MTP is necessary. Therefore, a new micro(µ )‐scale T ransfer rate O nline M easurement device (µTOM) was developed. The µTOM includes 96 parallel oxygen‐sensitive sensors and a single robust sealing mechanism. Different organisms ( Escherichia coli, Hansenula polymorpha, and Ustilago maydis ) were cultivated in the µTOM. The measurement precision for 96 parallel cultivations was 0.21 mmol·L −1 ·h −1 (pooled standard deviation). In total, a more than 15‐fold increase in throughput and an up to a 50‐fold decrease in media consumption, compared with the shake flask RAMOS‐technology, was achieved using the µTOM for OTR‐monitoring. Abstract : A new prototype device with small geometric footprint, the µTOM, allows monitoring of the oxygen transfer rate (OTR) in 96 deepwell microtiter plates. The device was used to monitor cultivations of common production organisms used in commercial biotechnology and research, such as Escherichia coli, Hansenula polymorpha ( Ogataea angusta ), and Ustilago maydis . For duplicate cultivations, including one reference condition, the µTOM allows the investigation of 47 new cultivation conditions in one experiment.